Diversity, distribution and abundance of bivalves in the vembanad backwaters - Christy, Ouseph (KUFOS, 2019)
Present study was conducted along the Vembanad backwaters with an aim to investigate the diversity, distribution and abundance of bivalves. Monthly sampling was done at 12 stations from northern, middle and southern regions of the backwaters. A total of 20 species, belonging to 8 orders, 9 families, and 17 genera were recorded based on which a checklist with updated IUCN status was prepared and presented. Of the eight orders, the dominant one was Venerida (30%) comprising 2 families and 6 species followed by Ostreida (15%), Arcida (15%), Mytilidae (10%), Cardiida (10%) and Pectinida (10%). Order Myida and Unionoida together contributed only <5% with a single species represented from each order viz., Martesia striata and Lamellidens marginalis respectively. Observation on the region wise diversity indices revealed that highest number of species (16- 19 species) recorded from middle estuarine region irrespective of. Villoritta cyprinoides the most dominant and widely distributed species was found absent middle estuarine region during all the three seasons. The relative abundance of V. cyprinoides was noticeably higher in Southern (99%) region than the northern region. Results of present study indicate that the V. cyprinoides ccupied in all the parts of Vembanad backwaters during all the seasons. In southern, middle, and northern regions seasonal biodiversity indices such as Margalef’s richness Index (d), Pieolu’s Evenness Index (J'), Shannon diversity index (H’), Simpson Index () and Simpson Dominance Index (1-) are calculated. In the middle estuarine region, the Species diversity was high. Mytilaster lineatus which is a fouling invasive bivalve species recorded from middle and northern regions of Vembanad backwaters; it’s abundance was relatively high in middle region i.e. 51% during monsoon followed northern region i.e.35% during monsoon.